Cerium(IV) ammonium nitrate: Reagent for the versatile oxidative functionalization of styrenes using N-hydroxyphthalimide. Issue 17 (26th April 2019) - Krylov, Igor B.; Paveliev, Stanislav A.; Matveeva, Olesya K.; Terent'ev, Alexander O.
Abstract: Cerium(IV) ammonium nitrate was found to be a versatile reagent for the oxidative functionalization of styrenes using N -hydroxyphthalimide and iodine affording three different types of products with oxyphthalimide, nitrate and iodide groups. It was shown that reaction of styrenes with N -hydroxyphthalimide and cerium(IV) ammonium nitrate can be selectively directed to oxynitro-oxyphthalimides and dioxyphthalimides depending on the reaction conditions, in particular a solvent. Reaction of styrenes with iodine under the action of N -hydroxyphthalimide and cerium(IV) ammonium nitrate leads to the formation of iodo-oxyphthalimides. Graphical abstract: Image 1